2012
DOI: 10.1364/ol.37.000425
|View full text |Cite
|
Sign up to set email alerts
|

Effect of emitter number on quantum cascade laser monolithic phased array

Abstract: We present the optical analysis of spatial single-mode monolithic quantum cascade laser arrays in the mid-IR. Subwavelength parallel microstripe waveguides are buried into InP:Fe and phase locked by evanescent coupling. Lasing at room temperature is obtained at λ=8.4 μm. We describe the near- and far-field of stripe arrays comprising up to 32 emitters. One hundred percent coherent emission is shown experimentally and well accounted for by a standard optical simulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…But, we show here that if a deterministic relative phase can be imposed upon devices in an array, then one can reduce the beam divergence and increase the output power by increasing the effective device emission surface. This cannot be achieved using evanescent coupling [17] or leaky-wave coupling via an antiguide configuration [18,19] given the extreme confining properties of metal-metal waveguides. Note however that Kao et al demonstrated a phase-locked array (up to 6 elements) of THz second-order, low-output-power DFB lasers using propagating wave coupling, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…But, we show here that if a deterministic relative phase can be imposed upon devices in an array, then one can reduce the beam divergence and increase the output power by increasing the effective device emission surface. This cannot be achieved using evanescent coupling [17] or leaky-wave coupling via an antiguide configuration [18,19] given the extreme confining properties of metal-metal waveguides. Note however that Kao et al demonstrated a phase-locked array (up to 6 elements) of THz second-order, low-output-power DFB lasers using propagating wave coupling, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in a wide‐ridge laser, a high‐order lateral mode will appear and lead to a bad far‐field profile. Naturally, the array is incorporated into the QCLs to achieve high output power [7]. However, the presence of gain only in the strong index region will favour the out‐of‐phase supermode, leading to at least a two lobes far‐field pattern for phase‐locked QCL array sources.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Recently, this technology has been demonstrated for QCLs by using an array of laser micro-stripes. 13,14 However, the experimental result reported so far indicated that the outof-phase operation is favored due to the reduced mode overlap between adjacent emitters and the additional propagation losses in the coupling region even though the geometrical array parameters have been adjusted as possible and gain of the active region is set high enough. 13 This out-of-phase mode of operation is not desirable in most cases since it gives a double-lobe far-field pattern with a large divergence angle.…”
mentioning
confidence: 99%